Application of the diastereoselective photodeconjugation of α,β-unsaturated esters to the synthesis of gymnastatin H - Raffier, Ludovic; Piva, Olivier (Beilstein Journal of Organic Chemistry, 2011)
The asymmetric synthesis of gymnastatin H has been achieved by using the photoisomerisation of a conjugated ester to its β,γ-unsaturated isomer through the protonation of a in situ generated dienol as key step. Thanks to diacetone D-glucose used as a chiral alkoxy group, the protonation occurred well onto one of the two diastereotopic faces with very high yields and selectivities. Moreover, by this way the configuration of the C-6 centre of the target molecule was controlled.
Keywords: amide; diastereoselective protonation; dienol; isomerisation; Wittig reaction

CRC Handbook of Organic Photochemistry and Photobiology - Piva, O. (Photodeconjugation of enones and carboxylic acid derivatives, 2004)

(untitled) - Jorgenson, M. J. (J. Chem. Soc., Chem. Commun., 1965)

(untitled) - Jorgenson, M. J.; Patumtevapibal, S. (Tetrahedron Lett., 1970)

(untitled) - Duhaime, R. M.; Weedon, A. C. (J. Am. Chem. Soc., 1987)

(untitled) - Piva, O.; Pete, J.-P. (Tetrahedron Lett., 1990)

(untitled) - Piva, O.; Pete, J.-P. (Tetrahedron: Asymmetry, 1992)

(untitled) - Piva, O. (J. Org. Chem., 1995)

(untitled) - Pelotier, B.; Holmes, T.; Piva, O. (Tetrahedron: Asymmetry, 2005)

(untitled) - Bargiggia, F.; Dos Santos, S.; Piva, O. (Synthesis, 2002)

(untitled) - Amagata, T.; Minoura, K.; Numata, A. (J. Nat. Prod., 2006)

(untitled) - Amagata, T.; Tanaka, M.; Yamada, T.; Minoura, K.; Numata, A. (J. Nat. Prod., 2008)

(untitled) - Fehlhaber, H. W.; Kogler, H.; Mukhopadhyay, T.; Vijayakumar, E. K. S.; Ganguli, B. N. (J. Am. Chem. Soc., 1988)

(untitled) - Buzzetti, F.; Gaümann, E.; Hütter, R.; Keller-Schierlein, W.; Neipp, L.; Prelog, V.; Zähner, H. (Pharm. Acta Helv., 1963)

(untitled) - Gurjar, M. K.; Bhaket, P. (Heterocycles, 2000)

(untitled) - Phoon, C. W.; Somanadhan, B.; Hui Heng, S. C.; Ngo, A.; Ng, S. B.; Butler, M. S.; Buss, A. D.; Sim, M. M. (Tetrahedron, 2004)

(untitled) - Murayama, K.; Tanabe, T.; Ishikawa, Y.; Nakamura, K.; Nishiyama, S. (Tetrahedron Lett., 2009)

(untitled) - Wipf, P.; Kim, Y.; Fritch, P. C. (J. Org. Chem., 1993)

(untitled) - Alcaraz, L.; Macdonald, G.; Ragot, J.; Lewis, N. J.; Taylor, R. J. K. (Tetrahedron, 1999)

(untitled) - Goldstein, S. W.; Overman, L. E.; Rabinowitz, M. H. (J. Org. Chem., 1992)

(untitled) - Nagaoka, H.; Kishi, Y. (Tetrahedron, 1981)

(untitled) - Zhdankin, V. V.; Stang, P. J. (Chem. Rev., 2002)

Activating agents and protection groups - Lygo, B. (1-Hydroxybenzotriazol, 1999)